Extrinsic Compression of Transplant Hepatic Artery by a Hemostatic Agent: “Surgiceloma” - Umar Tariq; Dimitra Landis; Anil Kotru; Ashok Bhanushali (The Arab Journal of Interventional Radiology)
A 38-year-old man who underwent liver transplantation was found to have absent vascular flow in the common hepatic artery (CHA) on Doppler ultrasound and angiogram 1 day after surgery. Surgical reexploration revealed a mass of expanded Surgicel compressing the CHA. Surgicel is an absorbable hemostatic agent used to control intraoperative bleeding. Blood flow was restored once the mass was removed, and the patient recovered uneventfully. Interventional radiologists need to recognize this finding of extrinsic vascular compression on hepatic angiogram to avoid unnecessary interventions. Furthermore, increased awareness of the clinical and imaging findings associated with compression of an artery by a “Surgiceloma” may increase the consideration of this phenomenon as a differential in the setting of postoperative impaired perfusion.